Effect of Mandatory Unit and Individual Physical Training on Fitness in Military Men and Women. Issue 5 (September 2017) - Anderson, Morgan K.; Grier, Tyson; Canham-Chervak, Michelle; Bushman, Timothy T.; Nindl, Bradley C.; Jones, Bruce H.
Purpose: The purpose of this study was to look at the effect of additional individual physical training (PT) in addition to mandatory unit PT as well as other risk factors on physical fitness. Design: A cross-sectional design. Setting: This study was conducted on a US military installation. Participants: Participants were 6290 male and 558 female active duty US Army soldiers in 3 light infantry brigades. Measures: Participants completed self-administered questionnaires asking about individual characteristics, PT, and physical fitness. Cut points were established for soldiers scoring within the top 33% for each of the 3 Army Physical Fitness Test events (2-mile run, sit-ups, and push-ups) and top 50% in each of the tests combined for overall performance. Analysis: Odds ratios and 95% confidence intervals from multivariate analyses were calculated. Results: Variables impacting physical fitness performance of men and women included increased body mass index, leading unit PT sessions, and individual distance running mileage. Other variables impacting physical performance for men included increased age, smoking, and individual resistance training. Conclusion: Soldiers performing additional individual PT demonstrated a positive influence on fitness compared to unit PT participation alone. Increased age and being overweight/obese negatively influenced physical fitness. To enhance fitness performance through unit PT, running by ability groups and resistance training should be encouraged by leadership.